PEMANFAATAN ANDROID DALAM DUNIA PENDIDIKAN - Verawati Verawati; Enny Comalasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper is in the form of a paper that aims to see the use of technology in the form of an Android cellphone in the world of Education. In the digital era, seeing the smallest events in the world can quickly be via mobile phones. The technological advancements that have arrived at Android phones make us able to grasp the world. Android can have a positive or negative impact depending on the use and utilization in everyday life, especially in the world of education. One form of technological advancements in Android phones is the playstore, which is one of the bridge programs to install other programs. One of the many programs to study the layout and provinces in Indonesia is the